2014 IEEE 26th International Conference on Tools With Artificial Intelligence 2014
DOI: 10.1109/ictai.2014.110
|View full text |Cite
|
Sign up to set email alerts
|

Diversification by Clauses Deletion Strategies in Portfolio Parallel SAT Solving

Abstract: Conflict based clause learning is known to be an important component in Modern SAT solving. Because of the exponential blow up of the size of learnt clauses database, maintaining a relevant and polynomially bounded set of learnt clauses is crucial for the efficiency of clause learning based SAT solvers. In this paper, we first compare several criteria for selecting the most relevant learnt clauses with a simple random selection strategy. We then propose new criteria allowing us to select relevant clauses w.r.t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…At a given search state, using a relevant selection function based on progress saving (PSM), it activates the most promising learned clauses while freezing irrelevant ones. In [11], a new criterion to quantify the relevance of a clause using its backtrack level called BTL for BackTrack Level was proposed. From experiments, the authors observed that the learned clauses with small BTL values are used more often in the unit propagation process than those with higher BTL values.…”
Section: On the Learned Clauses Database Management Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…At a given search state, using a relevant selection function based on progress saving (PSM), it activates the most promising learned clauses while freezing irrelevant ones. In [11], a new criterion to quantify the relevance of a clause using its backtrack level called BTL for BackTrack Level was proposed. From experiments, the authors observed that the learned clauses with small BTL values are used more often in the unit propagation process than those with higher BTL values.…”
Section: On the Learned Clauses Database Management Strategiesmentioning
confidence: 99%
“…Managing the learned clauses database was the subject of several studies [1,8,2,9,10,11]. These strategies were proposed with the objective to maintain a learned clause database of reasonable size by eliminating clauses deemed irrelevant to the subsequent search.…”
mentioning
confidence: 99%
“…At a given search state, using a relevant selection function based on progress saving (PSM), it activates the most promising learned clauses while freezing irrelevant ones. In [14], a new criterion to quantify the relevance of a clause using its backtrack level called BTL for BackTrack Level was proposed. From experiments, the authors observed that the learned clauses with small BTL values are used more often in the unit propagation process than those with higher BTL values.…”
Section: On the Learned Clauses Database Management Strategiesmentioning
confidence: 99%
“…Managing the learned clauses database was the subject of several studies [17,19,11,2,3,14]. These strategies were proposed with the objective to maintain a learned clause database of reasonable size by eliminating clauses deemed irrelevant to the subsequent search.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, keeping a lot of learned clauses slows down the propagation process, and may even cause the solver to run out of memory. Therefore, solvers clean their learned clause database regularly and delete some of the learned clauses [19,111,126,169].…”
Section: Clause Deletion Strategiesmentioning
confidence: 99%